Career decision making in undergraduate medical education - Sud, Shama; Premji, Laila; P. Wong, Jonathan; Punnett, Angela (Canadian Medical Education Journal, 2020)
Background: It is unclear how medical students prioritize different factors when selecting a specialty. With rising under and unemployment rates a novel approach to career counselling is becoming increasingly important. A better understanding of specialty selection could lead to improved career satisfaction amongst graduates while also meeting the health care needs of Canadians. Methods: Medical students from the University of Toronto participated in a two-phase study looking at factors impacting specialty selection. Phase I consisted of focus groups, conducted independently for each year, and Phase II was a 21-question electronic survey sent to all students. Results: Twenty-one students participated in the focus group phase and 95 in the survey phase. Primary themes related to career selection identified in Phase I in order of frequency included personal life factors (36), professional life factors (36), passion/interest (20), changing interests (19) and hidden curriculum (15). The survey phase had similar results with passion (83), lifestyle (79), flexibility (75), employment opportunities (60) and family (50) being ranked as the factors most important in specialty selection. Conclusion: Personal factors, professional factors and passion/interest may be key themes for medical students when deciding which specialty to pursue. Targeting career counselling around these areas may be important.